2020
DOI: 10.1101/2020.01.30.927277
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biotic and abiotic drivers of soil microbial functions across tree diversity experiments

Abstract: AimSoil microorganisms are essential for the functioning of terrestrial ecosystems. Although soil microbial communities and functions may be linked to the tree species composition and diversity of forests, there has been no comprehensive study of how general potential relationships are and if these are context-dependent. A global network of tree diversity experiments (TreeDivNet) allows for a first examination of tree diversity-soil microbial function relationships across environmental gradients.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 64 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…Cesarz et al . (2020) found that the strength of species richness effects on microbial functioning increases with age of the forest, hence it might be too early in forest development to find strong differences in biotic legacies. It is possible that the agricultural land‐use legacy overwhelms any potential tree species richness legacies at this young stage.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Cesarz et al . (2020) found that the strength of species richness effects on microbial functioning increases with age of the forest, hence it might be too early in forest development to find strong differences in biotic legacies. It is possible that the agricultural land‐use legacy overwhelms any potential tree species richness legacies at this young stage.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, effects of species richness are likely very context‐dependent (Cesarz et al . 2020). Previous studies have found long‐term effects of past agricultural land use, reporting higher pH and P concentration and lower organic matter content (Falkengren‐Grerup et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations